The Potential Anti-Photoaging Effect of Photodynamic Therapy Using Chlorin e6-Curcumin Conjugate in UVB-Irradiated Fibroblasts and Hairless Mice - Ga-Hee Hur; A-Reum Ryu; Yong-Wan Kim; Mi-Young Lee (Pharmaceutics, 2022)
Photodynamic therapy (PDT) has been used to treat cancers and non-malignant skin diseases. In this study, a chlorin e6–curcumin conjugate (Ce6-PEG-Cur), a combination of chlorin e6 (Ce6) and curcumin via a PEG linker, was used as a photosensitizer. The in vitro and in vivo effects of PDT using Ce6-PEG-Cur were analyzed in UVB-irradiated fibroblasts and hairless mice. The UVB-induced expression of MMPs was reduced in Hs68 fibroblast cells, and procollagen type Ⅰ expression was enhanced by Ce6-PEG-Cur-mediated PDT on a Western blotting gel. Moreover, UVB-induced collagen levels were restored upon application of Ce6-PEG-Cur-mediated PDT. Ce6-PEG-Cur-mediated PDT inhibited the expression of phosphorylated p38 in the MAPK signaling pathway, and it reduced the expression of phosphorylated NF-κB. In animal models, Ce6-PEG-Cur-mediated PDT inhibited the expression of MMPs, whereas procollagen type Ⅰ levels were enhanced in the dorsal skin of UVB-irradiated mice. Moreover, UVB-induced dorsal roughness was significantly reduced following Ce6-PEG-Cur-mediated PDT treatment. H&E staining and Masson’s trichrome staining showed that the thickness of the epidermal region was reduced, and the density of collagen fibers increased. Taken together, Ce6-PEG-Cur-mediated PDT might delay and improve skin photoaging by ultraviolet light, suggesting its potential for use as a more effective photo-aging treatment.